TElehealth in CHronic disease: mixed-methods study to develop the TECH conceptual model for intervention design and evaluation - Salisbury, Chris; Thomas, Clare; O'Cathain, Alicia; Rogers, Anne Elizabeth; Pope, Catherine; Yardley, Lucy; Hollinghurst, Sandra; Fahey, Tom; Lewis, Glyn; Large, Shirley; Edwards, Louisa; Rowsell, Alison; et al. (BMJ Publishing Group Ltd, 2015)
Objective To develop a conceptual model for effective use of telehealth in the management of chronic health conditions, and to use this to develop and evaluate an intervention for people with two exemplar conditions: raised cardiovascular disease risk and depression.